Cover Image. Issue 6 (1st June 2021) - Gu, Zhen‐Yi; Guo, Jin‐Zhi; Zhao, Xin‐Xin; Wang, Xiao‐Tong; Xie, Dan; Sun, Zhong‐Hui; Zhao, Chen‐De; Liang, Hao‐Jie; Li, Wen‐Hao; Wu, Xing‐Long
Abstract : Phosphate cathodes of sodium‐ion batteries usually exhibit low conductivity, seriously hinders their electrochemical properties. The authors (DOI: 10.1002/inf2.12184 ) of this manuscript regulate the fluorophosphate lattice with increased ionicity via aliovalent substitution, achieving the higher structural stability, improved electron/ion‐transport kinetics, and superior energy‐storage performances in advanced Na3.14 V1.93 Na0.07 (PO4 )2 F3 cathode. Abstract : Phosphate cathodes of sodium‐ion batteries usually exhibit low conductivity, seriously hinders their electrochemical properties. The authors (DOI: 10.1002/inf2.12184 ) of this manuscript regulate the fluorophosphate lattice with increased ionicity via aliovalent substitution, achieving the higher structural stability, improved electron/ion‐transport kinetics, and superior energy‐storage performances in advanced Na3.14 V1.93 Na0.07 (PO4 )2 F3 cathode.